Washington Luís Pereira de Sousa and the Urban Space Ordinance of the city of Batatais / SP - The Code of Postures of 1894 - Piccinato Junior, Dirceu (2019)
From the 1870s, coffee cultivation became the main condition of agriculture in the city of Batatais, in the state of São Paulo. This context caused a significant economic, social, political and cultural impetus, specially from the year 1886 with the arrival of the rails of the Cia. Mogiana de Estradas de Ferro in the city. Urban conditions were modest at the time and with the impact of the coffee complex the situation worsened: dirty streets, holes, lack of pavement, hygiene problems, sewage running in the open, became constant criticism. In the middle of this conflict, appears in the beginning of 1892 the figure of Washington Luís Pereira de Sousa, graduated from the Faculty of Law of Largo de San Francisco. Under this scenario, the present article aims to analyze and discuss the formation and performance of the "bachelor urbanist" Washington Luis through the Code of Postures prepared by him in 1894 for the city of Batatais.